The Venezuelan migration and its economic partner impact in the municipality of pamplona north of santander. - Arteada, Paola Andrea; Carvajal Villamizar, Andrés Felipe; Guerrero Jaimes, Ruth Mayerly (Universidad Francisco de Paula Santander, 2017)
Historically, the border between Colombia and Venezuela has bee none of the most dynamic. In these border crossings,the movement among citizens has been permanent, even a few decades ago Colombians traveled in search of apromising future to the neigh boring country and tourism was active. However, during the last decade, as a result of Venezuela's socio-economic situation and political and institutional instability, the population has been forced to seek new opportunities elsewhere, largely across the borders with Colombia.According to this situation, the municipality of Pamplona Norte de Santander is no stranger to this problem for thisreason, this project seeks to analyze the economic sectors with the greatest socio-economic impact that has beengenerated in themunicipality of Pamplona and the consequences and effects of these on the dynamics of the labor market and the economy.Given that the arrival of Venezuelan citizens who need to meet their basic need sand there fore generate in come has generate de conomic,cultural and social problems in the municipality.